Growing Medicinal Plants (Example of Silybum marianum) in Bukhara Region - Amonova, Gulshan Rustam qizi; Tuygunovna, Shukurova Shoxina; Rashidovna, Ostonova Gulnoza (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
This thesis provides information about the medicinal plants of the Bukhara region, their distribution areas, location on GIS maps, and their cultivation technology. It also addresses the importance of medicinal plants in pharmacy, methods for identifying medicinal species, and the use of ArcGIS tutorials on the distribution of medicinal species. It also includes detailed information on the distribution of milk thistle (Silybum marianum), its beneficial properties, and the cultivation technology of this plant. Data were collected via ethnobotanical surveys in the Bukhara region, using open and semi-structured interviews with 249 informants across all districts; resulting in documentation of 84 medicinal plant species from 72 genera and 39 families, mostly herbaceous species (94%). Cultivation experiments involved direct sowing of milk thistle seeds at 1-1.5 cm depth, row spacing of 40-75 cm and in-row spacing ~25 cm; sowing dates (early vs late spring) and seeding rates were varied to assess their effects on growth and seed. Biochemical analysis was performed on dry seed extracts via HPLC and mass spectrometry to quantify flavonolignans (such as silibinin, taxifolin, silichristin) and water-soluble vitamins.Ethnobotanical findings confirmed the use of 84 species, primarily herbaceous, used medicinally in traditional practice. Seed yield reached approximately 7 % of total plant biomass under optimal sowing conditions, matching data from regional comparisons. Biochemical profiling revealed high flavonolignan content (notably silibinin and taxifolin) in seeds from Uzbekistan, with antioxidant potential confirmed via mass spectrometry. This study defines optimal cultivation parameters for milk thistle in the Bukhara context (early spring sowing, standard spacing, moderated seeding rates). The shared ethnobotanical and phytochemical evidence supports the pharmaceutical value of milk thistle seeds and reinforces the relevance of traditional knowledge of medicinal plants in regional medicine.